How EFL materials respond to a local curriculum: A study of interest areas - López-Barrios, Mario Luis (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In formal education, the theme contents or interest areas included in EFL syllabuses are decided by the educational authority in accordance with national guidelines. In the Province of Córdoba, Argentina, these areas are named ámbitos de experiencia e interés, i.e., topics that relate to the experience and interests of the target learners including, apart from typical everyday situations, themes from the other curricular areas like science, social studies or art. Because some of these topics are controversial, publishers tend to minimise or exclude their presence in EFL materials. Despite their relevance, interest areas have scarcely been researched. Thus, this paper examines their presence in EFL materials used in some local schools and analyses them quantitatively and qualitatively to determine the breadth and depth of coverage of said topics. The study aims to raise awareness of the treatment of interest areas in EFL coursebooks and provide further insights in materials development.